2018
DOI: 10.1002/cnr2.1132
|View full text |Cite
|
Sign up to set email alerts
|

A new era of neoadjuvant treatment with Pertuzumab: Should the 10‐lymph node guideline for axillary lymph node dissection in breast cancer be revised?

Abstract: Background Pertuzumab has improved pathologic complete response rates when compared with other chemotherapeutics in the treatment of HER‐2 positive breast cancer patients. Aims We sought to determine if axillary lymph node dissections (ALNDs) yielding at least the national standard of 10 lymph nodes is lower in patients who received neoadjuvant pertuzumab. Methods and Results A retrospective database identified patients who underwent ALND for breast cancer. We compared the axillary lymph node retrieval rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…With the development of chemotherapy regimens and targeted anti-HER2 treatment, the primary tumor and axillary pCR rates have increased substantially. A previous study found that fewer than 10 lymph nodes were found in 41.7% of 139 breast cancer patients who underwent axillary dissection and received neoadjuvant pertuzumab, however in patients who received neoadjuvant chemotherapy but did not receive pertuzumab, only 18.6% of patients had less than 10 axillary lymph nodes dissected ( 37 ). Therefore, the low lymph node yield will underestimate the number of metastatic lymph nodes and may lead to improper prediction of prognosis and improper treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of chemotherapy regimens and targeted anti-HER2 treatment, the primary tumor and axillary pCR rates have increased substantially. A previous study found that fewer than 10 lymph nodes were found in 41.7% of 139 breast cancer patients who underwent axillary dissection and received neoadjuvant pertuzumab, however in patients who received neoadjuvant chemotherapy but did not receive pertuzumab, only 18.6% of patients had less than 10 axillary lymph nodes dissected ( 37 ). Therefore, the low lymph node yield will underestimate the number of metastatic lymph nodes and may lead to improper prediction of prognosis and improper treatment.…”
Section: Discussionmentioning
confidence: 99%